A rare case report: enlarged iliopsoas cystic solid mass associated with femoral head necrosis induced by heavy alcohol consumption. Issue 26 (June 2017) - Li, Chen; Liu, He; Wang, Chenyu; Han, Qing; Wang, Zhonghan; Qin, Yanguo; Wang, Jincheng; Yu, Tao
Abstract: Rationale: This article presents an unusual case of a large iliopsoas cystic solid mass associated with femoral head necrosis in a patient with heavy alcohol consumption for years. Patient concerns: The patient reported pain and limitation of movement at the right hip for 4 months. A soft tissue mass can be palpated deep in the groin several days after the onset of pain. Diagnoses: The laboratory assessments indicated an inflammatory response of the patient. Imaging was performed on the femoral head and iliopsoas cyst. The pathological feature of the mass was evaluated through biopsy examination. It was found that iliopsoas cystic solid mass is secondary to the femoral head necrosis induced by heavy alcohol consumption. Interventions: The patient underwent elective total hip arthroplasty. The bursa was excised and the anterior hip capsule closure was performed. Outcomes: After the surgery, imaging results showed a well-positioned prosthesis. At 1-year follow-up, the prosthesis was still well-positioned and no signs of recurrence of iliopsoas bursa were found. Lessons: We suggested the performance of elective total hip arthroplasty, bursa excision, and closure of the anterior hip capsule in patients with femoral necrosis and iliopsoas bursitis presented simultaneously.